Dialectics of Sharia Fintech Peer to Peer Lending: Opportunities and Challenges - Wardah Yuspin; Muhammad Edi Hermawan (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out some of the dialectical or problematic regulations of sharia-based peer to peer lending financial technology in Indonesia. The discussion in particular, this study explores the problems that arise related to the regulations used in Islamic peer to peer lending fintech which are regulated using the Financial Services Authority Regulation (POJK) Number 77 of 2016 concerning Information Technology-Based Lending and Borrowing Services. In addition, this study will also discuss the urgency behind the importance of establishing sharia-based fintech peer to peer lending regulations as well as ideas about content material that should be included in the formation of special regulations regarding sharia peer to peer lending fintech. This research is a library research through a statute approach. This research uses data collection method in the form of literature study. Through literature study, researchers collect documents and data to be processed using content analysis method. The results of this study indicate that in the regulation of sharia peer to peer lending fintech there are several problems related to the regulations used, the first is that POJK Number 77 of 2016 which is used to regulate sharia peer to peer lending fintech has more connotations of conventional peer to peer lending fintech , so that there is confusion in terms of separating the rules of conventional peer to peer lending from sharia peer to peer lending, Second, the emergence of legal uncertainty because currently sharia peer to peer lending fintech must comply with POJK rules Number 77 of 2016 and the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI Fatwa) Number 117 of 2018. Even though the fatwa should not be a statutory regulation that used to regulate because fatwas are not included in the hierarchy of laws and regulations according to Law Number 12 of 2011 concerning the Establishment of Legislations. Third, there is no regulation regarding the Sharia Supervisory Board in charge of supervising sharia compliance and is closely related to consumer protection, and fourth, POJK Number 11 of 2016 has not regulated in detail the dispute resolution mechanism